A cost-benefit analysis of document management strategies used at a financial institution in Zimbabwe: A case study - (:unkn) unknown (My University, 2013)
Background: Choosing a cost-effective document management approach has become a priority to many organisations, especially in view of the rapidly changing technological environment in which information is being created and managed. A literature survey indicated that document management strategies have the potential to provide some substantial cost-saving benefits if they are used judiciously.Objectives: This study investigated a commercial bank’s document management approaches in a bid to ascertain the costs and benefits of each strategy and related issues.Method: A quantitative research approach was employed through a case study which was used to gather data from a sampled population in the bank.Results: The document management approaches used were not coordinated to improve operational efficiency. There were regulations governing documents management. The skills and competences of staff on both document management and cost analysis are limited. That is partly due to limited training opportunities availed to them. That means that economies are not achieved in the management of records. That has a negative impact on the overall efficiency, effectiveness and legal compliance of the banking institution.Conclusion: The financial institutions should create regulations enabling periodical cost-benefit analysis of document management regimes used by the bank at least at quarterly intervals as recommended by the National Archives of Australia. A hybrid approach in managing records is recommended for adoption by the financial institution. There should be on-the-job staff training complimented by attendance at relevant workshops and seminars to improve the staff’s understanding of both the cost-benefit analysis concept and document management.
Keywords: African Research